Winter diet of the long-eared owl Asio otus (Strigiformes: Strigidae) in the grasslands of Janos, Chihuahua, Mexico. Issue 1 (December 2017) - González-Rojas, José; Padilla-Rangel, Hernaldo; Ruvalcaba-Ortega, Irene; Cruz-Nieto, Miguel; Canales-del-Castillo, Ricardo; Guzmán-Velasco, Antonio
Abstract Background The long-eared owl (Asio otus ) has a Holarctic distribution, including much of North America. This nocturnal species is considered to be extremely secretive, and poorly known in the Great Plains of the United States and Canada, as well as to México, where no previous studies on its diet have been conducted. Findings We analyzed 120 pellets collected during January 2007 in roosts in a 2–3 m height mesquite scrub within a grassland area of Reserva Ecológica El Uno, located in the Natural Protected Area Janos. We registered and identified three orders, four families, eight genera and ten species of mammals and two orders and one family of insects. Winter diet is dominated by mammals, especially rodents in both frequency and biomass. Cricetidae andPerognathus flavus were the most frequent family and species, respectively. On the other hand, when analyzing biomass, Sigmodon species were dominant, achieving almost 70% of the consumed biomass. Levin's standardized niche breath based on frequency was calculated as 0.40, while based on biomass was 0.38. Also, two previously unrecorded rodent species were identified as long-eared owl prey. Conclusion Although 18 different types of items were identified, the long-eared owl tends to be selective, with a single genera (Sigmodon ) comprising almost 70% of its consumed biomass during winter.Perognathus flavus was also important in frequency (21%); however, it barely constitutes 2% of the consumed biomass. Resumen El búho orejas largas es una especie Holártica, que se distribuye en gran parte de Norteamérica y que ha sido poco estudiada, especialmente en las Grandes Planicies de Estados Unidos y en México, donde no existe un estudio previo sobre su dieta invernal. Se colectaron y analizaron 120 egagrópilas en la Reserva Ecológica El Uno, dentro del Área Natural Protegida Reserva de la Biósfera Janos. Se identificaron un total de 18 tipos de presa, pero la especie mostró selectividad por dos géneros/especies, ya que cerca del 70% de la biomasa consumida fueron especies del géneroSigmodon, mientras que el 21% de las muestras conteníanPerognathus flavus . Además, dos especies de roedores identificadas constituyen nuevos registros de presa para la especie.